2018
DOI: 10.1111/1759-7714.12917
|View full text |Cite
|
Sign up to set email alerts
|

PD‐L1 expression in ROS1‐rearranged non‐small cell lung cancer: A study using simultaneous genotypic screening of EGFR, ALK, and ROS1

Abstract: BackgroundThe aim of the current study was to investigate the prevalence and clinicopathologic characteristics of ROS1‐rearranged non‐small cell lung cancer (NSCLC) in routine genotypic screening in conjunction with the study of PD‐L1 expression, a biomarker for first‐line treatment decisions.MethodsReflex simultaneous genotypic screening for EGFR by peptide nucleic acid clamping, and ALK and ROS1 by fluorescence in situ hybridization (FISH) was performed on consecutive NSCLC cases at the time of initial patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 47 publications
4
25
0
Order By: Relevance
“…13,14 It has been observed that up-regulated PD-L1 expression in NSCLC is correlated with oncogenic RAS signaling, while the tyrosine kinase ROS1 is involved in RAS signaling. 12,15 Most recently, high-level expression of PD-L1 has been associated with ROS1 rearrangement in NCSLC, 16,17 which is in line with other studies that PD-L1 expression in NSCLC is driven by aberrant activation of oncogenes (such as EGFR and ALK). [18][19][20][21] In this study, we found that PD-L1 expression was upregulated by ROS1 rearrangement through the MEK-ERK pathway signaling in NSCLC with Crizotinib resistance.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…13,14 It has been observed that up-regulated PD-L1 expression in NSCLC is correlated with oncogenic RAS signaling, while the tyrosine kinase ROS1 is involved in RAS signaling. 12,15 Most recently, high-level expression of PD-L1 has been associated with ROS1 rearrangement in NCSLC, 16,17 which is in line with other studies that PD-L1 expression in NSCLC is driven by aberrant activation of oncogenes (such as EGFR and ALK). [18][19][20][21] In this study, we found that PD-L1 expression was upregulated by ROS1 rearrangement through the MEK-ERK pathway signaling in NSCLC with Crizotinib resistance.…”
Section: Introductionsupporting
confidence: 80%
“…This finding is consistent with a recent report that high PD-L1 expression was significantly associated with ROS1 rearrangement in lung adenocarcinoma cohort. 16 Analyzing downstream signaling of ROS1 in response to Crizotinib (ROS1 inhibitor), we found depletion of PD-L1 expression was associated with the downregulation of MEK- ERK pathway signaling when HCC78 cells were treated with Crizotinib or ROS1 siRNAs. Our finding is in line with previous reported that PD-L1 expression is regulated through PI3K-AKT and RAS signaling in various solid tumors, as well as STAT3 or MEK-ERK pathway in some hematologic neoplasms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). However, this "intrinsic" mechanism of PD-L1 upregulation is contrasted by several recent clinical studies concluding that PD-L1 is highly expressed in EGFR-wildtype NSCLC [135], and there is a negative correlation [43,[136][137][138][139] or no significant correlation [135] between EGFR mutations and PD-L1 expression. One meta-analysis [139] revealed lower PD-L1 expression rates in EGFR-mutant than in EGFRwildtype tumors (36.7% vs 44.1%, P < 0.05).…”
Section: Egfr Mutations and Pd-l1 Expressionmentioning
confidence: 90%
“…Patients presenting at advanced stages and with unresectable lung tumors, which represent more than 70% of cases, have particularly benefitted. 2,10,[18][19][20][21][22][23][24][25][26] This can be partially attributed to basing therapeutic decisions on tumor typing, which is increasingly possible with cytology. The technological reach of molecular diagnosis has also allowed increasing prominence for cytopathology.…”
Section: Is Cytopathology the Flawed Shadow Of Surgical Pathology?mentioning
confidence: 99%